Ultrasensitive metadevice for biosensing - Chia, Daryl Hak Wee (Nanyang Technological University, 2021)
With the increase in demand for quality health screening, there is a need to improve the capability of current technology for biomolecule detection. This report introduces a metadevice that is capable of effective biomolecule detection at small amounts. Numerical experiments were carried out through Lumerical FDTD simulation with this metadevice to study the effects of graphene fermi energy level, scattering rate and electron mobility on the resonant reflection and transmission spectrum and thus, the absorption variation caused by the presence of a protein bound to the metadevice. This study gives us an insight on how a graphene plasmonic device may be able to detect biomolecules with a higher sensitivity through its molecular chemical fingerprint by detecting the biomolecule’s vibrational mode in the mid infrared region instead of using the traditional method of LSPR sensors where it mainly detects biomolecules using a change in refractive index.